Silence as a bridge of communication between the Sacred and the profane from the thought of Giles Lipovesky and Raimon Panikkar - Flores Olague, Roberto Gerardo (2025)
This text aims to expose the meaning of Silence and its connection with the Sacred as a constitutive part of the human being, as a human need to cross the borders of speech that fixes and delimits reality. For this, the ideas and postulates of Gilles Lipovestsky and Raimon Panikkar are presented. These authors, accompanied by the secondary voices of other thinkers of the 20th century, were defenders of the need for Silence and its connection with something Transcendent in the contemporary world, characterized by its noisy everyday life, attachment to the ephemeral and desacralized experiences.